Teachers’ perceptions on continuous professional development programs in international schools in Klang Valley - Edward Devadason; Babu Vengadasalam; Ng Yu Jin (Institute of Advanced Engineering and Science, 2026)
This study explores teachers’ perceptions of continuous professional development (CPD) initiatives in international schools within the vibrant educational landscape of Klang Valley. Through qualitative research methods, including interviews and observations, this paper investigates the factors influencing teachers’ engagement and the impact of CPD on teaching quality. The study involves nine teachers and two principals, offering diverse perspectives on their CPD experiences. Findings reveal that CPD programs are generally well-received, contributing to teachers’ ongoing growth, enhanced teaching skills, and improved classroom management in diverse settings. Key factors affecting CPD participation include time constraints and workload, program relevance, leadership support, financial limitations, and mismatched group dynamics, with time constraints and workload being particularly significant. Observations during CPD sessions demonstrate active teacher involvement. This research enriches existing knowledge by providing a comprehensive understanding of teacher perceptions of CPD in Klang Valley’s international schools. This study highlighted that the provision of CPD opportunities should be proposed and provided with teachers’ professional needs taken into consideration, and leadership should ensure these needs are met for maximum effectiveness. These findings have great implications for policymakers, school administrators, and educators with an interest in developing better CPD practices in international settings.